Pembentukan Goal Belajar Anak Usia Dini dalam Perspektif Teori Perkembangan Kognitif - Nerru Pranuta Murnaka; Devina Indah Christianti; Ratih Kusumo Wardani; Elizabeth W. M. Indira (PT. Penerbit Tiga Mutiara, 2026)
Early childhood is frequently understood as a golden period of development; therefore, the formulation of learning goals becomes a crucial component that influences the direction of children’s behavior, motivation, and engagement in the learning process. Problems arise when learning goals are predominantly formulated from an adult perspective, while the characteristics of children’s cognitive development are not fully taken into account, causing learning objectives to be difficult for children to understand and internalize. This study aims to examine the formation of learning goals for early childhood through the perspective of Jean Piaget’s cognitive development theory in order to obtain a conceptual understanding that is more aligned with children’s developmental stages. The research method employs a qualitative approach through a literature review of textbooks and national and international journal articles relevant to learning goals, cognitive development, and early childhood education, which are then analyzed descriptively through processes of identification, classification, and synthesis of theoretical concepts. The findings indicate that learning goals for early childhood tend to be concrete, short-term, contextual, and activity-oriented, and are not yet supported by mature self-regulation abilities. Based on Piaget’s framework, early childhood falls within the preoperational stage; therefore, understanding learning goals is highly dependent on direct experiences, play-based activities, simple symbols, and teacher guidance. The conclusion emphasizes that the design of learning goals must be consciously adjusted to children’s cognitive developmental stages so that learning objectives can be understood, meaningful, and optimally achieved. The novelty of this study lies in the conceptual integration of Piaget’s cognitive development theory with the practical formulation of learning goals in early childhood education as a theoretical–practical foundation for teachers.